2016
DOI: 10.1039/c6sc01301e
|View full text |Cite
|
Sign up to set email alerts
|

Gel permeation chromatography as a multifunctional processor for nanocrystal purification and on-column ligand exchange chemistry

Abstract: GPC provides a general approach to purification of a variety of nanocrystal types, and additionally achieves ligand exchange in a continuous flow system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 50 publications
0
62
0
Order By: Relevance
“…For further purification, gel permeation chromatography was used in the glovebox following literature procedures. [55][56] Purified material was stored as a stock solution in toluene in a N2 filled glovebox. Quantum dot solids were isolated by removing solvent under reduced pressure with a glovebox-attached cold trap.…”
Section: Methodsmentioning
confidence: 99%
“…For further purification, gel permeation chromatography was used in the glovebox following literature procedures. [55][56] Purified material was stored as a stock solution in toluene in a N2 filled glovebox. Quantum dot solids were isolated by removing solvent under reduced pressure with a glovebox-attached cold trap.…”
Section: Methodsmentioning
confidence: 99%
“…Gel permeation chromatography (GPC), a type of size exclusion chromatography (SEC), is an alternative approach to isolate CDs into fractions of different particle size [17,18] . When CDs are allowed to move through a column containing the gel, the small‐sized substances are able to penetrate into the gel particle pores while the large‐sized substances are excluded from the pores and pass directly through the column.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that low-dielectric-constant ester solvents were used as anti-solvents in the RP method to prevent damage during purification [5,16]. Herein, we demonstrate gel permeation chromatography (GPC) [17] with a nonpolar solvent, toluene, that can completely remove impurities via a one-cycle purification process in contrast to the conventional RP process. In addition, we demonstrated the effect of the interfacial layer between the hole transport layer and PeNC layer using alkyl ammonium salts containing Br anion, i.e., oleylamine bromide (OAm-Br), to passivate cation-and anion-defects [18].…”
Section: Introductionmentioning
confidence: 99%